Which scores need a core? An evaluation of MR-targeted biopsy yield by PIRADS score across different biopsy indications. Issue 4 (November 2018) - Sathianathen, Niranjan J.; Konety, Badrinath R.; Soubra, Ayman; Metzger, Gregory J.; Spilseth, Benjamin; Murugan, Paari; Weight, Christopher J.; Ordonez, Maria A.; Warlick, Christopher A.
Abstract Introduction Magnetic resonance imaging is being widely adopted in the clinical management of prostate cancer. The correlation of the Prostate Imaging Reporting and Data System (PIRADS) to the presence of cancer has been established but studies have primarily evaluated this in a single clinical setting. This study aims to characterize the correlation of PIRADS score to the diagnosis of cancer on fusion biopsy among men who are undergoing primary biopsy, those who have had a previous negative biopsy or men on active surveillance. Materials & Methods A consecutive sample of men undergoing US-MR biopsy at a single academic institution from 2014 to 2017 were included in this retrospective study. Men were stratified into groups according to their clinical history: biopsy-naïve, previous negative transrectal ultrasound (TRUS) biopsy or on active surveillance. The correlation of PIRADS score to the diagnosis of any and clinically significant cancer (Gleason score ≥ 3 + 4) was determined. Results A total of 255 patients with 365 discrete lesions were analyzed. PIRADS score 1–2, 3, 4 and 5 yielded any prostate cancer in 7.7, 29.7, 42.3 and 82.4% of the cases, respectively, across all indications while clinically significant cancer was found in 0, 8.9, 21.4 and 62.7%, respectively. The area under the receiver operative curves for the diagnosis of any and significant cancer was 0.69 (95%CI: 0.64–0.74) and 0.74 (95%CI: 0.69–0.79) respectively. Men who have had a previous negative biopsy had lower detection rates for any prostate cancer for PIRADS 3 and 4 lesions compared to those that were biopsy-naïve or on active surveillance. Conclusion Cancer detection rates are significantly associated with PIRADS score. Biopsy yields differ across biopsy indications which should be considered when selecting a PIRADS score threshold for biopsy. Biopsy of PIRADS 3 lesions could potentially be avoided in men who have previously undergone a negative TRUS biopsy.